Hubungan Penggunaan Gadget dengan Pekembangan Motorik pada Anak Pra Sekolah Usia 4-6 Tahun di TK Anggrek 97 Kabupaten Jember - Syaifuddin Syaifuddin; Rizka Rizka; Ro’isa Ro’isa (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Children who spend their play time playing with gadgets will tend to be lazy and reluctant to move around, so that their motor development process will be hampered. Motoric development in children also goes hand in hand with their physical maturity. Motor development is a physical activity that is centered on the brain, to acquire skills and increase the movement abilities of children to adults which are very necessary for controlling the body. This research aims to determine the correlation between gadget use and motor development in pre-school children aged 4-6 years at Anggrek 97 Kindergarten, Jember. This research method used correlational analysis with a cross sectional approach. The population was 45 students at Kindergarten Angrek 97 Jember, the sample size was 40 respondents, the sampling was determined using a purposive sampling technique. The instruments used questionnaire sheets for using gadgets and observation sheets for motor development. Then analyzed using Spearman rank test. The results of this study showed that 15 respondents (37.5%) had high gadget use and 22 respondents (55%) were starting to develop. The results of the analysis test p value = 0.000 < α 0.05. This means there is the correlation between gadget use and motor development in pre-school children aged 4-6 years at Anggrek 97 Kindergarten, Jember The role of parents has an important influence on the formation of character and the development of children, especially on their motor development and also to increase awareness of children in applying gadgets.